How Employee Motivation and Organizational Commitment Affect Workout Results - Syafruddin Kitta; Nurhaeda Zaeni (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2023)
The study's goal is to examine the impact of organizational motivation and commitment on productivity at the Makassar Multi Key Store. All 30 employees at the Multi Key Store in Makassar make up the population for this study. The census sampling method is used to ensure that a representative cross-section of the population is included. Primary data, collected from the results of respondents' surveys, is utilised. Descriptive statistics, tests of validity and reliability, tests of normality and multicollinearity and heteroscedasticity, and tests of hypotheses by means of multiple linear regression and the t test, the f test, and the determination coefficient are all part of the data analysis process. The findings of this study indicate, at least in part, that the motivation and dedication of each organization significantly and positively affect the performance of employees at the Makassar Multi Key Store. The study's findings reveal that both intrinsic motivation and organizational commitment have a substantial impact on productivity at Toko Multi Kunci Makasssar.